2020
DOI: 10.1371/journal.pone.0230603
|View full text |Cite
|
Sign up to set email alerts
|

Agency judgments in post-stroke patients with sensorimotor deficits

Abstract: Sense of agency refers to the feeling of being in control of one's actions. Previous research has demonstrated that sense of agency is produced through the sensorimotor system, which is involved in comparing internal predictions with sensory feedback in motor control. Therefore, sensorimotor deficits might impair agency through a sensorimotor system malfunction. The present study examined this hypothesis by investigating post-stroke patients who had suffered a subcortical stroke that damaged regions associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 67 publications
7
20
0
Order By: Relevance
“…Regarding the results of motor performance, the difference in movement errors between the SELF and OTHER conditions was observed in each experiment week. This result replicates that of the previous studies [15,16,32], suggesting that PA and PB correctly completed the movement tasks, just like the participants in their previous studies did. Although movement errors of PA were greater in the OTHER condition than those of PB, there were no obvious differences in movement errors across the second, fourth, and eighth weeks in the performances of PA and PB.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Regarding the results of motor performance, the difference in movement errors between the SELF and OTHER conditions was observed in each experiment week. This result replicates that of the previous studies [15,16,32], suggesting that PA and PB correctly completed the movement tasks, just like the participants in their previous studies did. Although movement errors of PA were greater in the OTHER condition than those of PB, there were no obvious differences in movement errors across the second, fourth, and eighth weeks in the performances of PA and PB.…”
Section: Discussionsupporting
confidence: 89%
“…This modification was done because we focused on the self-other attributions in a nonparalyzed upper limb use, and we needed to reduce the number of experiments to ease the burden on the patients as much as possible. The previous study confirmed that there were no significant differences in self-other judgments between the right and left upper limb uses [15].…”
Section: Methodssupporting
confidence: 75%
See 3 more Smart Citations